Performance evaluation of hollow fiber air gap membrane distillation module with multiple cooling channels - Aryapratama, Rio; Koo, Heoncheol; Jeong, Seongpil; Lee, Seockheon (ELSEVIER SCIENCE BV, 2016)
The hollow fiber air gap membrane distillation (AGMD) module equipped with the multiple cooling channels network made of stainless steel was developed. The performance of the developed AGMD module was evaluated by conducting several experiments, including the effect of feed temperature and flow rate, ratio of membrane surface area to condensation surface area, membrane packing position, comparison with hollow fiber DCMD, and the effect of inner and outer module channels to process performance. Moreover, theoretical model was suggested for the multiple cooling channels module. This study reveals that the produced flux and thermal efficiency of this module were up to 12.5 kg/m(2) h and 81.7%, respectively, which is higher than most of previous studies that used polymeric fibers as coolant channels. Furthermore, the optimum ratio of membrane area to condensation surface area to produce optimum flux and thermal efficiency is known to be around 0.55. Further experimental results show that the outer channel has significant contribution in reducing the amount of heat loss. This is also could be the reason why the average flux of hollow fiber AGMD module was only 22% lower, while the average thermal efficiency is 58% higher than that of hollow fiber DCMD module. (C) 2016 Published by Elsevier B.V.
Keywords: DIRECT-CONTACT; DESALINATION; CHALLENGES; EFFICIENCY; MODEL